Awareness and Perception about Health Insurance among People at a Sub-metropolitan City of Nepal - Kapar, Vijay Kumar; Shah, Laxmi; Sah, Neha; Shah, Poonam (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Health insurance is a type of insurance coverage that pays for medical, surgical and sometimes dental expenses incurred by the insured. It reimburses the insured for expenses incurred from illness or injury or pays the case provider directly. The objective of this study is to determine awareness and perception about health insurance among people of Janakpurdham. MATERIALS AND METHODS: A cross sectional study, using simple random sampling among 400 participants was done at Janakpurdham. A semi structured questionnaire was used. Data was tabulated, categorized and was analyzed using statistical methods JASP version. Chi-square test was used to find out the association between the dependent and independent variables. RESULTS: In this research awareness about health insurance among respondents slightly more than one third 137(34.25%) were heard about health insurance and 293(73.25%) heard about health insurance scheme. Maximum number of respondents received information from friends 154(38.5%) followed by public media 127(31.7%) and few from newspaper 96(24.0%), and few from employment were 23 (5.8%). Higher Socio-economic status of the respondents were found to be significantly associated with more awareness on health insurance. CONCLUSIONS: Awareness about health insurance was satisfactory, but it did not lead to increased enrolment. There is a need to reinforce information, education and communication campaign about health insurance among the general population.